Prove the following identities: i) (1+ tan^2 A) + (1 + 1/ tan^2 A) = 1/ sin^2 A – sin^4 A ii) (cos^2 A -1)(cot^2 A + 1) = -1 iii) (sinTheta

Question

Prove the following identities: i) (1+ tan^2 A) + (1 + 1/ tan^2 A) = 1/ sin^2 A – sin^4 A ii) (cos^2 A -1)(cot^2 A + 1) = -1 iii) (sinTheta + secTheta)^2 + (cosTheta + cosec Theta)^2 = (1 + cosecTheta sec Theta)^2 iv) (1 + cot Theta – cosec Theta)(1 + tan Theta + sec Theta) = 2 v) tan^3 Theta/1 + tan^2 Theta + cot^3 Theta/ 1 + cot^2 Theta = sec Theta cosec Theta – 2 sin Theta cos Theta vi) 1/sec Theta + tan Theta – 1/ cos Theta = 1/ cos Theta – 1/sec Theta – tan Theta vii) sin Theta / 1 + cos Theta + 1 + cos Theta / sin Theta = 2 cosec Theta viii) tan Theta / sec Theta – 1 = sec Theta + 1 /tan Theta ix) cot Theta / cosec Theta – 1 = cosec Theta + 1 / cot Theta x) (sec A + cos A)(sec A – cos A) = tan^2 A + sin^2 A xi) 1+ 3 cosec^2 Theta + cot^6 Theta = cosec^6 Theta xii) 1 – sec Theta + tan Theta / 1 + sec Theta – tan Theta = sec Theta + tan Theta -1/ sec Theta + tan Theta + 1​

in progress 0
Sophia 1 month 2021-08-23T04:47:53+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-08-23T04:49:34+00:00

    Answer:

    v

    Step-by-step explanation:

    I hope that you can see

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )